Coupled Coincidence and Common Fixed Point Theorems in Menger PM Spaces - singh, Drdeepak; Ahmed, Amin; Rathore, M. S. (International Journal of Applied Mathematical Research, 2012)
Recently Many results on coupled xed point theory exist in the literature, for more de-tails, one can see in [2,11,22]. We established coupled coincidence and common xed point theoremsfor two self mixed g-monotone mappings in the settings of Menger PM-spaces. Our result is alsosubstantiated with the aid of an appropriate example and some open problems are also suggestedfor further studies